Strategies Used by Engineering Graphics and Design Teachers to Support Progressed Learners in Bridging Content Gaps: Teachers’ Perspectives on Foundational Knowledge Gaps and Learner Support - Siphesihle Eugene Mthethwa; Mogale Simon Albert Maeko; Douglas Thembinkosi Sotsaka (Universitas Majalengka, 2026)
This study explored the strategies used by Engineering Graphics and Design (EGD) teachers to support progressed learners in bridging content knowledge gaps. The study was motivated by the persistent underperformance of progressed learners in EGD, particularly in tasks requiring spatial visualisation and the application of foundational drawing principles. The study aimed to examine teachers’ perceptions of these content knowledge gaps and identify the strategies used to address them. A qualitative research approach within the interpretivist paradigm was employed. Data were collected through semi-structured interviews with eight EGD teachers from seven secondary schools and analysed using Braun and Clarke’s thematic analysis approach. The findings revealed that progressed learners experience challenges related to spatial visualisation, orthographic projection, isometric drawing, assembly drawing, and analytical tasks. Teachers attributed these challenges to weak foundational knowledge acquired during Grade 9 Technology, poor retention of concepts, and difficulties in applying drawing conventions consistently. The findings further showed that inadequate foundational knowledge negatively affects learners’ ability to cope with advanced EGD concepts in the Further Education and Training phase. The study concludes that strengthened foundational instruction, targeted learner support, and effective intervention strategies are essential for improving learner performance in EGD.